2018
DOI: 10.1055/s-0038-1660830
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinical Outcome after Reconstruction of Complex Soft Tissue Defects Involving the Achilles Tendon with the Composite Anterolateral Thigh Flap with Vascularized Fascia Lata

Abstract: The ALT-FL flap enables reconstruction of complex tissue defects involving the Achilles tendon with good functional results. However, the presence of an increased BMI or PAD, but not necessarily the age, proves to be a predictor of poor clinical outcome and therefore should be subject to scrutiny during patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
0
20
0
3
Order By: Relevance
“…41,42 However, ALT flap is also limited by demanding microsurgery, vascular crisis, and secondary thinning procedures for bulky flap. 43 The sural flap can be harvested easily without vascular anastomosis and has reliable blood supply without sacrificing the main vessel of leg.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 However, ALT flap is also limited by demanding microsurgery, vascular crisis, and secondary thinning procedures for bulky flap. 43 The sural flap can be harvested easily without vascular anastomosis and has reliable blood supply without sacrificing the main vessel of leg.…”
Section: Discussionmentioning
confidence: 99%
“…29 The composite anterolateral thigh flap with the fascia lata has been widely applied in Achilles region, especially in massive deficit. [30][31][32] There are some unignorable drawbacks including vascular crisis, secondary thinning procedures for bulky flap and deficit of quadriceps femoris muscle contraction forces. 2,31 The radial forearm flap with palmaris longus tendon provides thin and pliable integument and long tendon, while it has significant donorsite morbidity and is better suited for small rather than massive defects.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] There are some unignorable drawbacks including vascular crisis, secondary thinning procedures for bulky flap and deficit of quadriceps femoris muscle contraction forces. 2,31 The radial forearm flap with palmaris longus tendon provides thin and pliable integument and long tendon, while it has significant donorsite morbidity and is better suited for small rather than massive defects. 33,34 Dobke et al 35 reported satisfactory outcomes of the extended temporoparietal fasciagaleal flap for a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The finding in this study that BMI did not affect outcomes is in disagreement with earlier studies. 16,23 Olsson et al 24 concluded that a high BMI predicted a worse ATRS at both 6 and 12 months, but no correlation was found with heel-rise height.…”
Section: Discussionmentioning
confidence: 99%